CONTINUOUS GLUCOSE MONITORING IN DIABETES MANAGEMENT: CLINICAL BENEFITS AND THE ROLE OF FREESTYLE LIBRE - Terbosh, Magda; Dubaj , Magdalena; Ignarska, Justyna; Judzińska, Alicja; Kubicz Mzabi, Sabina; Kwolek , Marlena; Osipowska, Julia; Piech, Bartosz; Sobczyńska, Kamila; Trojanowska , Emilia (International Journal of Innovative Technologies in Social Science, 2026)
Diabetes poses a significant public health challenge and requires effective methods for monitoring and managing glucose levels. Traditional approaches, such as glycated hemoglobin (HbA1c) and self-monitoring of blood glucose (SMBG), have important limitations, including a limited ability to assess glycemic variability and detect hypoglycemic episodes. This study aims to present the development of continuous glucose monitoring (CGM) technologies, evaluate their impact on metabolic control and patients’ quality of life, and analyze the role of the FreeStyle Libre system in modern diabetes care. This literature review is based on an analysis of randomized controlled trials, observational studies, and clinical guidelines regarding CGM use. Real-world data and recent evidence on the development of diabetes technologies were also included. The findings indicate that CGM use is associated with improved glycemic control, including reduced HbA1c levels, increased time in range (TIR), and fewer hypoglycemic episodes. The FreeStyle Libre system, as an example of flash glucose monitoring technology, is particularly effective in reducing hypoglycemia, while real-world data suggest additional improvements in HbA1c levels. In summary, CGM represents a key component of modern diabetes care, enabling a more precise and personalized approach to treatment and supporting the digital transformation of healthcare.